Editorial - Konečnik Kotnik, Eva (Journal for Geography, 2020)
This issue of Revija za geografijo/Journal for Geography is one of those with which we especially want to pay tribute to the memory of one of the founding members of the Department of Geography. It is dedicated to Professor Ludvik Olas, who would have celebrated his ninetieth birthday in 2020. With nine articles, we connect to the fields and areas of Olas's life and work. The words of Dr. Božidar Kert are very meaningful, who twenty years ago described Olas as a personality equally committed to geographical "research" and "teaching". This combination of aspects refers not only to Professor Olas, a respected professor of geography didactics, vividly present in the memories of many geography teachers who studied in Maribor and one of the founders of modern geography didactics in Slovenia, but also to the comprehensive mission of the Department of Geography at the University of Maribor. It's about the intertwining of geographical research and the inclusive collaboration, monitoring, and encouragement of young people in creating their future and the future of the World.